Strategi Pemasaran Rumah Makan Minang Di Kecamatan Alam Barajo Kota Jambi - Chiara Aristha Putri; Nazori Majid; Lidya Anggraeni (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
This study aims to find out how the marketing strategy used by Minang restaurants, Alam Barajo District, Jambi City, an Islamic review of the marketing strategies used by Minang restaurants, Alam Barajo District, Jambi City, and how to develop Minang restaurants in Alam Barajo District, Jambi City so that they remain exist. This research is a qualitative type. The object of this research is a Minang restaurant located in Alam Barajo District, Jambi City. The data sources used are primary data and secondary data. Data were obtained directly from respondents, totaling 15 Minang restaurants by conducting data analysis methods, namely observation, interviews and personal documentation, then the data was processed using data processing techniques. The results showed that: The marketing strategy carried out by Minang restaurants in Alam Barajo District, Jambi City used an average of 4p, namely place, product, price promotion. The Islamic Economic Review of the marketing strategy carried out by Minang restaurants in Jambi City District can be concluded, that Minang restaurants are in accordance with an Islamic perspective on average carrying out marketing strategies by setting prices, providing the best quality products, Minang restaurants are one of the a creative business that is superior because of the unique taste and use of a variety of native Indonesian spices that are difficult to imitate by other food products.